Spirits of Life and Perception - Meroni, Michele, author.
1 online resource (548 pages)
Keywords: Does a plant shrink at night and swell in the day, like an animal breathing in and out? For a long time, the Galenic concept of spiritus provided a causal explanation for human and animal life and perception. Albert the Great (1200-1280), whose honorific acknowledges among other things his pioneering work on biology, extended the concept to plants. This is only one of the remarkable concepts studied in this book, the first comparative study of Albert's concept of spiritus. It unveils the Arabic roots of his early psychophysiology and the original developments found in his mature Aristotelian paraphrases.